Салихат: роман : [16+] / Наталья Елецкая - Елецкая Наталья Владимировнва (Это личное!, 2022)
Экземпляры: ф. 2 (20231005) / Инвентарный номер: 121591 / Цена: 374.00 / Авт.знак: Е 50 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6